Web-Based Coat an Kebaya Rental Information System in Palembang City - Apriansyah, Apriansyah; Sobrina, Khoirunnisa Nabila; Haryanto, Dedi (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
That study's objective is to develop and develop a web-based information system for renting suits and kebaya in Palembang City. This system is expected to facilitate the process of renting traditional clothing, especially suits and kebayas, for various events and occasions. The system will provide an online platform for customers to browse and select available Suits and Kebayas, make online reservations, and track their rental status. The system will also allow rental service providers to manage inventory, update availability, and accept online payments. The proposed system is expected to boost productivity and effectiveness of the renting procedure, increase customer satisfaction, and increase the competitiveness of rental service providers in Palembang City. The system will be developed using a web-based approach, and its functionality will be evaluated through usability testing and user acceptance testing. Because the information presented basically comes from input data (input), then before entering data you must check the data correctness of data so that the resulting information is appropriate. Prepare hardware and software support whose specifications can support this system well. Perform periodic data back-ups to anticipate undesirable events. This system cannot only be used for one place. It is hoped that this system can be used in all places or areas where the system is not yet computerized to save time and energy.